Lá fora... na rua é diferente!: adolescência, escola e sintoma - Márcio Boaventura Júnior (2012)
Relevant theme of interest for the researches of psychoanalysis and education alike, adolescence has been ranking higher and higher in todays contemporary theories. But, after all, who is this adolescent subject? What does an adolescent say and what type of speeches does he make about himself and the place he occupies in society, especially in the school context. Based on speeches collected from conversations with teenagers from the municipal public school system of Belo Horizonte, we might suppose the configuration of a close almost a motherly complicity between teacher and pupil that might be contributing to fixating adolescence in a denial mechanism of sexual difference.